Evaluation of inhalable and respirable particulate matter in a museum gallery - Nur Baiti binti Mat Husin (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2019)
The primary idea of this research is to evaluate the inhalable and respirable particulate matter in the museum gallery of the National Museum Malaysia. Present study was conducted in Gallery A and Gallery B of the National Museum, Kuala Lumpur during January 2017. Temperature, Relative Humidity, Total Inhalable particulates and Respirable particulates were measured inside the galleries, stone, metal and ceramic artefact display cases at every 60 minutes interval for 8 hours between 9:00 AM to 5:00 PM. The average particulate matter concentration at the museum entrance (243 µg/m3) and lobby (382 µg/m3) was recorded much higher than the standard proposed by the Department of Environment (50 µg/m3) and Department of Occupational Safety and Health (150 µg/m3). Studies shown that, the concentration of inhalable and respirable particulates in Gallery A during weekday exposure was higher than the weekend exposure. The inhalable particulates mass concentration recorded was 127 µg/m3 and 92 µg/m3 for weekday and weekend exposure respectively. Meanwhile for respirable particulates mass concentration, the value recorded in weekday was 210 µg/m3 and weekend was 74 µg/m3. High number of tourists and heavy traffic near Jalan Damansara and construction of Muzium Negara MRT Station could be attributed to significantly higher concentration of PM10 in the museum building. However, there was significant variation in the mass concentration inside artefact display cases of Gallery A and Gallery B. The average temperature recorded in the museum gallery was 23 ̊C to 28 ̊C, and average relative humidity measured was 44 % to 60 %. Both temperature and relative humidity value are close to the limit of the American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE) class A's which means no mechanical risk to the most of artefact in the museum gallery. This study is beneficial towards Jabatan Muzium Malaysia by emphasizing that maintenance of Heating, Ventilation and Air Conditioning (HVAC) and regular monitoring of temperature and relative humidity inside museum are significantly influence the mass concentration. Hence, measures should be taken in minimizing the long term effect of particulate matter towards deterioration of artefact exhibited inside the National Museum and also to improve a better indoor air quality of the museum.